Assessing the sustainability status of mangrove forest ecosystem management by coastal community in Jaring Halus Village, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sahputra E, Harahap RH, Wahyuningsih H, Utomo B. 2021. Assessing the sustainability status of mangrove forest ecosystem management by coastal community in Jaring Halus Village, North Sumatra, Indonesia. Biodiversitas 22: 1-9. Mangrove forest ecosystems provide various important ecological (physical and protection) and economic services. Mangrove forest needs to be sustainably managed to ensure their functions and benefits are available in perpetuity. Still, issues regarding sustainable management of mangrove forests are rarely discussed, especially in Indonesia. This research aims: (i) to gain the fundamental understanding of the level of sustainable mangrove management by determining indicator attributes that can be categorized as leverage factors; ii) obtain the perceptions of coastal communities in mangrove forest management; and iii) investigate the compliance of coastal communities in mangrove forest management. Data were obtained through a series of interviews, field observation and focused group discussion (FGD) and questionnaires conducted from January 2018 to March 2019 in Jaring Halus Village, Secanggang Subdistrict, Langkat District, North Sumatra, Indonesia. Data were analyzed using multidimensional scaling (MDS). The results showed that the status of mangrove forest management in Jaring Halus Village was categorized as moderately sustainable with a score of 65.83%. The majority of the coastal community (96% of respondents) perceived and understood the value of protecting the mangrove ecosystem, which provided physical (ecological), economic, and social functions. The community's understanding and knowledge of the importance of mangrove forests is due to the high level of dependency on their main livelihood as fishermen. Around 97% of the respondents held strong obedience to the mangrove forest management in Jaring Halus Village, which could be attributed to local wisdom related to natural resource management.